From Berlin to Kigali: the sobering journey of acute respiratory distress syndrome - Bein, Thomas (Journal of Thoracic Disease; Vol 8, No 5 (May 01, 2016): Journal of Thoracic Disease, 2016)
What do Berlin, Kigali, and acute respiratory distress syndrome (ARDS) have in common? Berlin is the capital of Germany, brimming with attractiveness, science, culture, and a great lifestyle after the re-unification 25 years ago. Kigali is the largest city in Rwanda as well as its capital since the country’s independence in 1962, located at an altitude of 1,560 m. ARDS is characterized by dysregulated inflammation, inappropriate accumulation of leukocytes, uncontrolled activation of coagulation, and alveolar barrier disruption (1), often resulting in a life-threatening impairment of pulmonary gas exchange with hypoxemia, hypercapnia, and respiratory acidosis. The main causes of ARDS are direct (pneumonia, aspiration of gastric content) or indirect injuries (sepsis, massive transfusion, multi-trauma, peritonitis, pancreatitis). In European countries, the incidence of ARDS was estimated to be 50 cases per 100,000 person years, corresponding to approximately 40,000 cases per year for a country like Germany (2). ARDS is often associated with multiple-organ failure. A broad scenario of acute interventions for ARDS therapy have been investigated and recommended in recent years, but evidence that all these measures can decrease mortality is still limited (3). Mortality remains as high as 40–50% in major series (4).